The Influence of Hofstede's Cultural Dimensions on Job Satisfaction: A Study of African Expatriates in Turkey - Amanor, Samuel; Demirel, Hatice Gökçe (My University, 2023)
This article investigates the influence of Hofstede's six cultural dimensions on job satisfaction among African expatriates working in Turkey. The study specifically focuses on the dimensions of Indulgence-Restraint, Individualism-Collectivism, Uncertainty Avoidance, Masculinity-Femininity, Power Distance, and Long-Short term orientation. A hierarchical regression model was employed to analyse the data collected through a survey questionnaire administered to legally employed African individuals from Ghana, Nigeria, South Africa, and Ethiopia. Results revealed that all five dimensions—Indulgence-Restraint, Individualism-Collectivism, Uncertainty Avoidance, Masculinity-Femininity, and Power Distance—displayed a significant relationship with job satisfaction. These dimensions exerted varying degrees of influence on job satisfaction, suggesting that cultural factors significantly influence the overall job satisfaction levels of African expatriates in Turkey. However, it is worth noting that no significant relationship was found between Long-Short term orientation and job satisfaction among the participants. This implies that this particular dimension may not play a prominent role in influencing job satisfaction among the surveyed African expatriates. The findings contribute to the existing body of knowledge on the intersection of cultural dimensions and job satisfaction, specifically within the context of African expatriates in Turkey. The results highlight the importance of understanding and considering cultural factors when examining job satisfaction levels among individuals from different cultural backgrounds.
Keywords: Culture; Job Satisfaction; Cultural Dimensions; African Expatriates